2021
DOI: 10.3390/w13060858
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Pelagic Fish Community Composition, Abundance, and Biomass along a Productivity Gradient in Subtropical Lakes

Abstract: How fish communities change with eutrophication in temperate lakes is well documented, while only a few studies are available from subtropical lakes. We investigate the fish community structure in 36 lakes located in the Yangtze River basin, covering a wide nutrient gradient. We found that fish species richness and total fish catch per unit effort (CPUE) increased significantly with chlorophyll a (Chla). Among the different feeding types, the proportion of zooplanktivores increased significantly with Chla, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 65 publications
(127 reference statements)
1
10
0
Order By: Relevance
“…Common carp Cyprinus carpio was chosen as our model benthivorous fish species. It is the most widely distributed freshwater fish, has successfully invaded or naturalized in many countries world-wide, including Asia, Europe, America and Australia (Vilizzi et al, 2015) and is a common species in Chinese lakes containing the two test macrophyte species (Guo et al, 2010;Li, Fan, et al, 2017;Yu et al, 2021). We used juvenile carp to arrive at a realistic fish density (see below).…”
Section: Macrophyte and Fish Speciesmentioning
confidence: 99%
“…Common carp Cyprinus carpio was chosen as our model benthivorous fish species. It is the most widely distributed freshwater fish, has successfully invaded or naturalized in many countries world-wide, including Asia, Europe, America and Australia (Vilizzi et al, 2015) and is a common species in Chinese lakes containing the two test macrophyte species (Guo et al, 2010;Li, Fan, et al, 2017;Yu et al, 2021). We used juvenile carp to arrive at a realistic fish density (see below).…”
Section: Macrophyte and Fish Speciesmentioning
confidence: 99%
“…High abundances of small-bodied fishes can reduce species diversity within fish communities and affect the complexity and stability of ecosystems (Lima et al, 2016;Liu et al, 2017). Some studies demonstrated that the overabundance of small-bodied fishes and declines in overall fish diversity were accompanied by the deterioration of water quality (Karr, 1981(Karr, , 1991Karr et al, 1986;Yu et al, 2021). Moreover, the present study revealed a significant reduction in the Shannon-Wiener diversity index, the Pielou evenness index and the Simpson's diversity index of fishes inhabiting the Mangshe River versus Lake Yanlong.…”
Section: Discussion Spatial Patterns In Fish Community Compositionmentioning
confidence: 99%
“…Eutrophication enhances phytoplankton biomass (Wetzel, 2000), which generally leads to higher total fish biomass and density (Brucet et al, 2013;Jeppesen et al, 2000;Yu et al, 2021). However, while planktivorous and omnivorous fish benefit from eutrophication (Robertis et al, 2003;Yu et al, 2021), the feeding efficiency of piscivorous fish is often reduced, in part due to the high water turbidity and competition with other fish at the juvenile stage (Jeppesen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Larger and deeper lakes usually have higher fish richness and abundance due to their wider range of microhabitats and greater stability than smaller and shallower lakes (Brucet et al, 2013; Drakou et al, 2009; Olin et al, 2002). Eutrophication enhances phytoplankton biomass (Wetzel, 2000), which generally leads to higher total fish biomass and density (Brucet et al, 2013; Jeppesen et al, 2000; Yu et al, 2021). However, while planktivorous and omnivorous fish benefit from eutrophication (Robertis et al, 2003; Yu et al, 2021), the feeding efficiency of piscivorous fish is often reduced, in part due to the high water turbidity and competition with other fish at the juvenile stage (Jeppesen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%